2022
DOI: 10.3389/fsurg.2022.972561
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation and risk assessment after splenectomy in hepatolenticular degeneration patients associated with hypersplenism

Abstract: BackgroundBoth hepatolenticular degeneration (HLD) and viral hepatitis B (HBV) can cause hypersplenism, but whether splenectomy is needed or can be performed in HLD patients associated with hypersplenism is still controversial. At present, HLD combined with hypersplenism has not been listed as the indication of splenectomy.ObjectiveThis study aimed to investigate the efficacy, risks, and postoperative complications of splenectomy in HLD patients associated with hypersplenism.MethodsWe retrospectively analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…As the disease progresses, hepatic injury can gradually advance to liver fibrosis, eventually leading to cirrhosis. In clinical practice, complications such as gastrointestinal bleeding, hepatic encephalopathy, infection, portal vein thrombosis, or spongiform transformation often occur (25). Studies have shown that ∼35-45% of patients, regardless of whether their main manifestation is liver damage, neuropsychiatric symptoms, or if they are asymptomatic, have cirrhosis at the time of WD diagnosis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, hepatic injury can gradually advance to liver fibrosis, eventually leading to cirrhosis. In clinical practice, complications such as gastrointestinal bleeding, hepatic encephalopathy, infection, portal vein thrombosis, or spongiform transformation often occur (25). Studies have shown that ∼35-45% of patients, regardless of whether their main manifestation is liver damage, neuropsychiatric symptoms, or if they are asymptomatic, have cirrhosis at the time of WD diagnosis (26,27).…”
Section: Discussionmentioning
confidence: 99%